Raising Soil Organic Matter Content to Improve Water Holding Capacity - Jehangir H. Bhadha; Jay M. Capasso; Raju Khatiwada; Stewart Swanson; Christopher LaBorde (EDIS)
This article highlights the importance of raising soil organic matter in sandy and calcareous soils as it relates to increasing the water holding capacity of the soil. Farming in Florida on sandy soils has numerous limiting factors; one of which is it's low water holding capacity. By raising the soil organic matter content by just 1% can have a significant increase in soil water holding capacity. This would mean that soil would be able to hold more water for long durations. The prospect of increasiong water holding capacity in soils is great for agricultural productivity, and can have a significant impact on water conservation and usage.